The Impact of Diabetes Education by Clinical Pharmacist on Quality of Life and Treatment Satisfaction of Sudanese Individuals With Type II Diabetes Mellitus: Randomized, Double-Blind, Controlled Trial - Safaa Badi; Sara Zainelabdein Suliman; Rayan Almahdi; Mohammed A. Aldomah; Mohamed H. Ahmed; Habab Khalid Elkheir; Mohamed Izham Mohamed Ibrahim (SAGE Publishing, 2024)
Background: Patients' satisfaction with their treatment directly impacts the control of their diabetes. Quality of life is crucial for patients with diabetes mellitus to maintain long-term health and minimize complications. The current study aimed to evaluate the impact of diabetes education on quality of life (QoL) and treatment satisfaction of patients with type 2 diabetes mellitus. Methods: The current study was a randomized controlled trial. Patients with type 2 diabetes who were attending the diabetes clinic for 1 year were recruited. The overall sample in this study was 364 participants; 182 controls 182 cases. The interventional and control group participants were assigned randomly by simple random sampling technique. Controls were managed per usual care while cases were managed per usual care plus education done by the researcher. Pre-structured standardized questionnaires were used to collect the data. Data were processed and analyzed by using SPSS; version 28. Results: More than three-fourth of the participants; 76.4% were females. The average (±SD) age of the cases was 54.5 (±10) years, while was 56 (±9.8) years for controls. The overall median (IQR) years of DM diagnosis for all participants was 8 (4-14) years. The results showed a statistically significant difference between the mean satisfaction score from baseline to 12 months in the cases compared the controls ( P  < .001). Furthermore, there are statistically insignificant differences between the changes of mean overall QoL score from baseline to 12 months among the 2 groups. Conclusion: The education provided improved self-reported treatment-satisfaction among individuals with diabetes .A statistically insignificant differences in QoL between the 2 groups compared to baseline have been shown at the study end. The trial registration number is PACTR202311766174946 which was registered by pan African clinical trials registry, https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=26928 .